The social project housing postwar France - Cupers, Kenny 1977- (University of Minnesota Press, 2014)
" In the three decades following World War II, the French government engaged in one of the twentieth century's greatest social and architectural experiments: transforming a mostly rural country into a modernized urban nation. Through the state-sanctioned construction of mass housing and development of towns on the outskirts of existing cities, a new world materialized where sixty years ago little more than cabbage and cottages existed.Known as the banlieue, the suburban landscapes that make up much of contemporary France are near-opposites of the historic cities they surround. Although these postwar environments of towers, slabs, and megastructures are often seen as a single utopian blueprint gone awry, Kenny Cupers demonstrates that their construction was instead driven by the intense aspirations and anxieties of a broad range of people. Narrating the complex interactions between architects, planners, policy makers, inhabitants, and social scientists, he shows how postwar dwelling was caught between the purview of the welfare state and the rise of mass consumerism.The Social Project unearths three decades of architectural and social experiments centered on the dwelling environment as it became an object of modernization, an everyday site of citizen participation, and a domain of social scientific expertise. Beyond state intervention, it was this new regime of knowledge production that made postwar modernism mainstream. The first comprehensive history of these wide-ranging urban projects, this book reveals how housing in postwar France shaped both contemporary urbanity and modern architecture"..
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1945-2000; ARCHITECTURE / History / Contemporary (1945-); SOCIAL SCIENCE / Sociology / Urban; ARCHITECTURE / Urban & Land Use Planning; Geschichte; Stadtplanung; City planning -- France -- History -- 20th century; Housing -- France -- History -- 20th century; Architecture and state -- France -- History -- 20th century; Architecture and society -- France -- History -- 20th century; Städtebau; Wohnungspolitik; Wohnungsbau; Stadtsoziologie; Frankreich